A novel method for developing three dimensional (3D) silk–PVA microenvironments for bone tissue engineering—an in vitro study. (30th January 2018) - Pillai, Mamatha M; Elakkiya, V; Lakshmipriya, H; Gopinathan, J; Selvakumar, R; Bhattacharyya, Amitava
Abstract: Three dimensional (3D) porous scaffold based bone tissue engineering can possibly serve as an alternative approach to repairing severe bone injuries. The present study was carried out to evaluate the impact of 3D porous silk fibroin (SF)–polyvinyl alcohol (PVA) based scaffolds on human osteoblast-like (MG63) cell attachment and proliferation in vitro . SF and PVA blended porous scaffolds (3:1 ratio) with tunable porosity and mechanical properties were prepared by a freeze drying method in a solvent-free system. Citric acid plays a dual role of cross-linking and a gas foaming reaction with sodium bicarbonate (NaHCO3 ). Porosity was induced by gas foaming using different weight fractions (0.5%, 1.0%, 1.5% and 2.0% w/v) of NaHCO3 . The developed scaffolds were characterized for porosity, swelling ratio, compressive and biodegradation properties. The scaffolds were proved to be non-toxic to the osteoblast-like cells in MTT assay. The DNA content of the cells attached to the scaffolds was also estimated. The cell attachment and proliferation onto the scaffolds were studied using SEM. The study highlights the potential of such 3D scaffolds with controlled porosity as an effective biomaterial for bone regeneration.